Love (and other disasters) - Keshishian, Alek; Murphy, Brittany, 1977-2009; Rhys, Matthew, 1974-; Cabrera, Santiago; Bloom, Orlando, 1977-; Paltrow, Gwyneth, 1972-; EuropaCorp; Skyline (LoD) Limited; Ruby Films (Firm); Canal+ España (Firm) ([S.l.] : 3L, 2009)
An assistant at British "Vogue," Jacks adores fixing up her friends, but when it comes to finding the right guy for herself, she's totally clueless. Love comes knocking at her door when she meets sexy photographer Paolo, but will she dare to let her guard down and let romance in?
Extras: Making of -- Interview Britanny Murphy -- Trailer.
Director of photography, Pierre Morel ; editor, Nick Arthurs ; music composer, Alexandre Azaria ; costume designer, Michel Clapton ; production designer, Alice Normington.
Brittany Murphy, Matthew Rhys, Santiago Cabrera, Orlando Bloom and Gwyneth Paltrow.
FSK rating: 6 years or more.
DVD, region 2, anamorphic widescreen (1.85:1) ; Dolby Digital 5.1 surround, Dolby Digital 2.0.
In English dubbed German.
Keywords: Love -- England -- London -- Drama; Man-woman relationships -- England -- London -- Drama; Feature films; Comedy films